A Review of the Turnaround in Iranian Foreign Policy during President Hassan Rohani’s Administration - Haghgoo, Javad; Ghaffari Hashjin, Zahed; Aghaei, Mohammad (Journal of History Culture and Art Research, 2017)
The transition of power in the Islamic Republic of Iran is not only a change of guards in the different political and executive institutions during each electoral cycle but it also radically redefines the fundamental aspects of self-identity and the very definition of national interests and priorities and even how they should be defined. Upon the assumption of power by President Hassan Rohani in Iran, foreign policy of the government of the Islamic Republic of Iran has been exposed to tremendous developments. Prevalence of conservatism over revolutionary mindset, nationalism over trans-nationalism, and structuralism over agent-oriented trends are considered as the three main pillars of these developments. In Rohani’s administration there is no longer any trace of the revolutionary behavior of Ahmadinejad’s era. This turnaround in the Islamic Republic of Iran’s foreign policy is not a new phenomenon. We have witnessed such a shift in Iranian foreign policy after the end of the 8-year war with Iraq, albeit with different dimensions. An assessment of this issue would greatly enhance our understanding of the country’s foreign policy. Accordingly, assessment of the real roots of these foreign policy shifts is the main objective of the present article. Evidently, the shift in foreign policy, more than anything else can be attributed to changes in the definition of the concept of national interests, and how each administration defines such national and transnational interests. Any shift or transformation in this concept, as the guiding principal of foreign policy, creates a context for the shift in the national priorities, orientations, and strategies in its interaction with its external environment. By highlighting the three concepts of “circulation of elites”, “perception towards national identity”, and “structural developments”, the present article endeavors to review the causes of differing understandings of the concept of national interests in a specific period of the I.R. of Iran’s foreign policy.